The Knock-Out Rule under the UPICC as a Mechanism for Resolving the Battle of Forms in Indonesia - Sandra Salwa Afifah; Laina Rafianti; Helitha Novianty Muchtar (Dinasti Research, 2026)
The development of modern commerce, characterized by the widespread use of standard contractual documents and electronic transactions, has given rise to the phenomenon of battle of forms, namely situations in which parties proceed with a transaction despite the existence of mutually inconsistent standard clauses. This phenomenon challenges the classical construction of contract formation under the Indonesian Civil Code (KUHPerdata), which is grounded in the theory of offer and acceptance requiring strict correspondence between the two. This study aims to analyze how the knock-out rule as stipulated in Article 2.1.22 of the UNIDROIT Principles of International Commercial Contracts (UPICC) contributes to legal certainty in resolving conflicts of standard terms and to examine its relevance within the Indonesian contract law system. Employing a normative juridical method with statutory and comparative approaches between the KUHPerdata and the UPICC as a soft law instrument, this research finds that the knock-out rule provides a more adaptive framework by recognizing the existence of a contract insofar as the parties have agreed on its essential elements, while disregarding conflicting clauses and replacing them with applicable gap-filling provisions. This principle maintains a balance between freedom of contract, good faith, and legal certainty, and has the potential to address normative gaps in Indonesian contract law while promoting harmonization with international commercial practice.